Venetoclax Combined With FLAG-IDA Induction and Consolidation in Newly Diagnosed and Relapsed or Refractory Acute Myeloid Leukemia. Issue 25 (1st September 2021) - DiNardo, Courtney D.; Lachowiez, Curtis A.; Takahashi, Koichi; Loghavi, Sanam; Xiao, Lianchun; Kadia, Tapan; Daver, Naval; Adeoti, Maria; Short, Nicholas J.; Sasaki, Koji; Wang, Sa; Borthakur, Gautam; et al.
Abstract : PURPOSE: Sixty percent of newly diagnosed patients with acute myeloid leukemia (ND-AML) receiving frontline therapy attain a complete response (CR), yet 30%-40% of patients relapse. Relapsed or refractory AML (R/R-AML) remains a particularly adverse population necessitating improved therapeutic options. This phase Ib/II study evaluated the safety and efficacy of fludarabine, cytarabine, granulocyte colony-stimulating factor, and idarubicin combined with the B-cell lymphoma-2 inhibitor venetoclax in ND-AML and R/R-AML. MATERIALS AND METHODS: The phase IB portion (PIB) enrolled patients with R/R-AML using a 3 + 3 dose escalation and de-escalation algorithm for identification of maximum tolerated dose and dose-limiting toxicities. The phase II portion enrolled patients into two arms to evaluate response and time-to-event end points: phase IIA (PIIA): ND-AML and phase IIB (PIIB): R/R-AML. RESULTS: Sixty-eight patients have enrolled to date (PIB, 16; PIIA, 29; PIIB, 23). Median age was 46 years (range, 20-73). Grade 3 and 4 adverse events occurring in ≥ 10% of patients included febrile neutropenia (50%), bacteremia (35%), pneumonia (28%), and sepsis (12%). The overall response rate for PIB, PIIA, and PIIB was 75%, 97%, and 70% with 75%, 90%, and 61%, respectively, achieving a composite CR. Measurable residual disease–negative composite CR was attained in 96% of ND-AML and 69% of R/R-AML patients. After a median follow-up of 12 months, median overall survival (OS) for both PII cohorts was not reached. Fifty-six percent of patients proceeded to allogeneic hematopoietic stem-cell transplantation (ND-AML, 69%; R/R-AML, 46%). In R/R-AML, allogeneic hematopoietic stem-cell transplantation resulted in a significant improvement in OS (median OS, NR; 1-year OS, 87%). One-year survival post-HSCT was 94% in ND-AML and 78% in R/R-AML. CONCLUSION: Fludarabine, cytarabine, granulocyte colony-stimulating factor, and idarubicin + venetoclax represents an effective intensive treatment regimen in ND-AML and R/R-AML patients, associated with deep remissions and a high rate of transition to successful transplantation.